Non-oxidative reforming of methane in a mini-gliding arc discharge reactor: Effects of feed methane concentration, feed flow rate, electrode gap distance, residence time, and catalyst distance - Rueangjitt N. (2014)
In this work, a mini-gliding arc discharge reactor was employed for the reforming of methane under ambient temperature and pressure operation. Acetylene and hydrogen were produced dominantly with high selectivities of ~70-90 and ~75%, respectively. The results showed that both methane conversion and product selectivities depended strongly on various operating parameters, including feed methane concentration, feed flow rate, electrode gap distance, residence time, and the presence of a reforming catalyst (as a function of catalyst distance). The Ni catalyst-loaded porous alumina-silica plate was used to study the catalytic effect on the process performance at various residence times. A considerable enhancement of methane conversion and product yields was achieved in the combined plasma-catalytic system, particularly at a longer residence time. The catalyst distance, or packing position of catalyst plate, was also found to be an important factor affecting the process performance of the combined plasma-catalytic methane reforming. The closer catalyst distance led to the greater methane conversion because of the greater possibility of adsorption-desorption interactions of excited gaseous species on the catalyst surface to enhance subsequent reactions. © 2011 Springer Science+Business Media, LLC.